Analysis of flutter characteristics of ultra-large horizontal axis wind turbine blades at low rotor speed - Ma, Lu; Qin, Ming; Zhang, Xianfeng; Shen, Xin; Wang, Su (Frontiers in Energy Research, 2025)
As the blade size of wind turbine ascends, the potential flutter issue has become a crucial factor in the safety design of wind turbines. The high flexibility and strong nonlinearity result in the possibility of flutter for ultra-large horizontal axis wind turbine blades even at low rotor speed. With the IEA 15 MW wind turbine blade as the research object, the dynamic model of the wind turbine blade aeroelastic system was established. Research on the aeroelastic response during flutter at low rotational speeds and the multi-degree-of-freedom coupling characteristics therein was conducted. The results indicate that under the operating conditions of low rotational speed and high wind speed, the wind turbine blade can undergo multi-degree-of-freedom coupled flutter involving flapwise-edgewise-torsional coupling. Only the edgewise-torsional coupling characteristics are presented in the frequency domain. However, from the energy perspective, it is found that the flutter is maintained by the combined work of the aerodynamic forces in all three degrees of freedom. Different blade segments contribute differently, and the middle section and the tip of the blade make the main contribution. There exists a distinct coupling phenomenon in the development of the instantaneous aerodynamic power of each degree of freedom.